WOMAN’S STRUGGLE TOWARDS STEREOTYPES IN THE CASE OF THE MISSING MARQUESS: AN ENOLA HOLMES MYSTERY - St Murensi Dinda Saputri; Neisya Neisya (Elite : English and Literature Journal, 2021)
This research tries to analyze the women’s struggle towards stereotypes in the novel The Case of The Missing Marquess: An Enola Holmes Mystery. The objectives of this research are to identify, classify and analyze the phenomena of the historical picture of stereotypes for women in the 18th century pictured in the novel, and how the women struggled with the stereotypes in it. This was qualitative research with descriptive method. The researcher utilized the liberal feminism theory by Mary Wollstonecraft in analyzing the data. First, the researchers tried to find out how was the historical women's struggles at that time and after that found out characters who struggled with stereotypes in the novel. The result of this research was the character shows how she struggles to find her mother in terms of seizing the right to vote for women, and Enola, the main character, changes people's views about women at that time. Enola was also an illustration that not all women had to followed the rules or became a standard for a good figure, but it was freedom and courage that could change people's views of women that women could also do things without the helped of men and women were entitled to the same rights as men.